MLT544 : Clinical chemistry I / Faculty of Health Science - UiTM, Faculty of Health Sciences (Universiti Teknologi MARA (UiTM), 2021)
This course introduces the principles of clinical chemistry with emphasis in the laboratory testing methods pertaining to each of the topic discussed. Diagnostic and laboratory test procedures and interpretations will be detailed for the routinely ordered tests and selected special tests. The clinical significance of these tests is addressed for the commonly ordered tests to serve as a guide and reference for accurate reporting of results.